Колективна відповідальність держав-учасниць угоди про уніфікований патентний суд при порушенні права ЄС - Маринів, І. (НДІ ПЗІР НАПрН України, 2023)
Стаття присвячена аналізу характеру та обсягу зобов’язань, взятих на себе державами-учасницями Угоди про Уніфікований патентний суд (англ. UPC Agreement), а також Регламентів № 1257/2012 про поширення співробітництва у сфері створення єдиної системи патентної охорони і № 1260/2012 про поширення співробітництва у сфері створення єдиної системи патентної охорони щодо відповідних положень про переклад, що входять до так званого «патентного пакету». Предметом дослідження є відповідальність держав-членів Європейського Союзу за зобов’язання, які виникли як наслідок їх участі в механізмі посиленої співпраці та підписання Угоди про Уніфікований патентний суд, а також процесуальні механізми притягнення до відповідальності за їх порушення. Проведено аналіз правової бази, що регулює правосуб’єктність Уніфікованого патентного суду Європейського Союзу зокрема положень, що регламентують співробітництво Уніфікованого патентного суду Європейського Союзу з Судом справедливості Європейського Союзу, використання ним права Європейського Союзу при прийнятті рішень, а також відповідальність, що покладається на держави при порушенні права Європейського Союзу в результаті діяльності Уніфікованого патентного суду. Означено проблеми та виклики, які можуть виникнути після початку роботи Уніфікованого патентного суду, зокрема звернено увагу на відсутність деталізованого механізму регулювання питання колективної відповідальності держав-учасниць Угоди про Єдиний патентний суд перед Судом Європейського Союзу. Визначено можливі наслідки порушення права Європейського Союзу та оцінені вірогідні стратегії, якими може скористатися Суд справедливості Європейського Союзу для притягнення держав до відповідальності, визначення характеру такої відповідальності та її обсягу. Перелічено недоліки певних методів накладення санкцій на учасників Угоди, зокрема оцінено ефективність фінансових санкцій, зважаючи на фінансову автономність Уніфікованого патентного суду Європейського Союзу. Запропоновано можливі альтернативи, до яких потенційно може звернутися Суд Європейського Союзу для більш ефективного захисту цілісності acquis Європейського Союзу, зважаючи на унікальну правову природу Уніфікованого патентного суду. Зроблено висновки про проблеми та виклики, які стоятимуть перед інституціями ЄС, державами-членами, що беруть участь в посиленій співпраці з приводу Єдиного європейського патенту, а також самим Уніфікованим патентним судом Європейського Союзу як судом, який уособлює держави-члени Угоди, що робить його взаємодію з правопорядком Європейського Союзу безпрецедентним правовим явищем. Problem setting. This article is devoted to the analysis of the scope of obligations, accepted by the Contracting States in the Agreement on a Unified Patent Court, as well as in the EU Regulations № 1257/2012 on implementing enhanced cooperation in the area of the creation of unitary patent protection and № 1260/2012 on implementing enhanced cooperation in the area of the creation of unitary patent protection with regard to the applicable translation arrangements, that all form the so-called «patent pack». The subject of this research is EU Member States’ responsibility for the obligations, deriving from their activity via the enhanced cooperation mechanism and the procedural models of them being held responsible for the possible EU law infringements. The analysis of the legal base, governing the legal personality of the Unified Patent Court, including the clauses, that outline the interactions between the Unified Patent Court and the European court of justice, has been conducted. The problems and probable challenges, that will have appeared when the Unified Patent Court becomes operational, have been set, primarily stressing the problem of absence of a detailed Contracting Member States’ collective liability provision within the Agreement on a Unified Patent Court. Probable outcomes of EU law infringements have been detected and the available strategies, that can be used by the Court of Justice of the European Union for enforcing liability on the Member States and ruling its decisions on the scope and severity of such a liability, have been discovered. The conclusion about the problems and challenges, that might appear before the EU institutions, Member States, taking part in the enhanced cooperation concerning the creation of the Unified Patent Court, which will impersonate the Contracting States of the Agreement of a Unified Patent Court, has been made. Analysis of recent researches and publications. The issues of the legal nature of the Unified Patent Court and the nature of collective and individual responsibility of the member states of the Unified Patent Court Agreement were considered in the publications of the following researchers: Douwe de Lange, Jacopo Alberti, Alfredo Ilardi, Aurora Plomer, James Tumbridge, Jelena Cerani, Franklin Dehousse, Franklin Dehousse. Target of the research is to study a complex nature of the issue of individual and collective liability of the Contracting States via the Unified Patent Court agreement and to outline the possible ways of fulfilling the flaws of its legal regulation. Article’s main body. The legal rules, governing the Unified Patent Court’s liability are set in Chapter IV of the Agreement on a Unified Patent Court. Article 20 of the Agreement on a Unified Patent Court points at the EU law primacy principle, which reads as follows: «the Court shall apply Union law in its entirety and shall respect its primacy». Moreover, article 21 of the Agreement on a Unified Patent Court gives the Unified Patent Court the right to request preliminary rulings from the Court of Justice of the European Union, the decisions of which appear to be binding on the Unified Patent Court. In case of EU law infringement, the liability for the damages shall be incurred upon the Contracting States of the Agreement on a Unified Patent Court collectively and severally, in accordance with the EU law governing the Member States’ non-contractual liability for damages caused by the infringements of the EU Law, that result from the faulty application of the EU law by the national courts of the Member States. According to the provisions of article 23 of the Agreement of a Unified Patent Court, the Unified Patent Court’s actions shall be directly attributed to each Contracting State, concerning the scope of articles 258 – 260 of the Treaty on the functioning of the European Union. The rules in these articles cover the actions of the Commission of the European Union regarding the summaries, made by this institution in case of a reasonable suspicion of the Member State’s EU law infringements, involving a lawsuit to the Court of Justice of the European Union. The aspect of the liability and damages, conferred by the Court of Justice of the European Union on the Member State, are worth being made a detailed research of further in this paper. Conclusions and prospects for the development. To sum this up, it’s worth noting, that the problem of EU Member States’ liability for taking action of harmonizing the field of patent law by means of an international treaty must be considered in light of an unprecedented legal nature of the Unified Patent Court. The analysis of the legal construction, governing the future activity of the Unified Patent Court can be hardly described as the only and the most complicated problem, which might actually arise as soon as the Unified Patent Court becomes operational. Nevertheless, the Member States of the EU have managed to make a truly daring step forward towards the patent law unification, that can only be praised as a remarkable event in the history of the Union, that will surely entail more challenges for the EU Member States and institutions. However, such an outstanding experiment, in case of its success, may create an attractive harmonization instrument for the EU Member States in the foreseeable future.
Keywords: Єдиний патентний суд; санкції; Суд справедливості Європейського Союзу; Unified Patent Court; European Court of Justice; liability; damages